Transition‐Metal‐Free Carbon Isotope Exchange of Phenyl Acetic Acids - Destro, Gianluca; Horkka, Kaisa; Loreau, Olivier; Buisson, David‐Alexandre; Kingston, Lee; Del Vecchio, Antonio; Schou, Magnus; Elmore, Charles S.; Taran, Frédéric; Cantat, Thibault; Audisio, Davide (Angewandte Chemie International Edition, 2020)
A transition‐metal‐free carbon isotope exchange procedure on phenyl acetic acids is described. Utilizing the universal precursor CO2, this protocol allows the carbon isotope to be inserted into the carboxylic acid position, with no need of precursor synthesis. This procedure enabled the labeling of 15 pharmaceuticals and was compatible with carbon isotopes [14C] and [13C]. A proof of concept with [11C] was also obtained with low molar activity valuable for distribution studies. Just labeled: Transition‐metal‐free carbon isotope exchange on phenyl acetic acids is described. Utilizing the universal precursor CO2, the carbon isotope can be inserted into the carboxylic acid position, with no need of precursor synthesis. This procedure enabled the labeling of 15 pharmaceuticals and was compatible with [14C] and [13C]. A proof of concept with [11C] was also obtained with low molar activity valuable for distribution studies.